(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Plants provide natural molecules as an effective agent for phytomedicine. Anticancer properties of natural products are well described. Several studies on hydroxychavicol (HCH), and plumbagin (PLB), which are found in Piper betle leaf and Plumbago sp. respectively, are evidenced as anti-carcinogenic effect on chronic myeloid leukemic (CML) cells through increased reactive oxygen species (ROS). An attempt was taken to determine the efficacy of a new combination of HCH and PLB on CML cells (K562) and the mechanism of apoptosis thereon. 3-4,5-Dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide (MTT) assay was performed to determine the dose for individual and combination treatments of HCH and PLB against leukemic cells, (K562). Apoptotic activity was assessed through flow cytometric analysis with annexin V-FITC/propidium iodide staining. Immunoblots were also performed on cell extracts before and after the treatments. Levels of ROS and nitric oxide (NO) in K562 cells were measured by DCF-DA and DAF-FM staining, respectively. In addition, P38 and JNK siRNA transfection were performed to assess the roles of mitogen-activated protein kinase (MAPK) pathways on apoptosis. Combination treatments of HCH (16 μM) and PLB (0.5 μM) showed synergistic effects on reducing viability and increased cellular apoptosis of K562 cells. Combined treatments showed elevated reactive oxygen species (ROS) and NO levels than individual treatments of HCH and PLB. Moreover, decreasing the ROS generations by antioxidants/catalase reversed cell deaths and increased viability. Immunoblotting of MAPK pathways components showed reduction of pERK levels, while upregulation pJNK and pP38 levels upon HCH+PLB treatments. Furthermore, silencing of JNK and/or P38 rescued the K562 cells from deaths. The present study indicates combination treatments of HCH and PLB act as a better therapeutic against CML by promoting MAPK-mediated apoptosis via increased oxidative and nitrosative stress. This in vitro approach is the first report describing the mechanism of action of HCH/PLB to fight against Leukemia via interaction with phosphorylated P38.